A Study of The Assessment for Boron Neutron Capture Therapy Agent - Isman Mulyadi Triatmoko; Sutjipto Sutjipto (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2017)
A study of the assessment criteria covers the synthesis and characterization of agent and test their biological effectiveness as boron neutron capture therapy (BNCT) agents in cancer treatment. The cellular uptake of this agent into the glioblastoma cells was assessed by boron analysis (ICP-MS) and by fluorescence imaging (confocal microscopy). The agent enters the glioblastoma cells exhibiting a similar profile, i.e., preferential accumulation in the cytoskeleton and membranes and a low cytotoxic activity (IC50 values higher than 200 μM). The cytotoxic activity and cellular morphological alterations after neutron irradiation in the Research Reactor (>107 neutrons cm−2 s−1) were assessed by the MTT assay and by electron microscopy (TEM). Post neutron irradiation revealed that BNCT has a higher cytotoxic effect on the glioblastoma cells. Results provide a strong rationale for considering one of these compounds as a lead candidate for a new BNCT agent.